Asuhan Kebidanan Continuity of Care Ny. EL Umur 34 Tahun di UPTD Puskesmas Ainiba - Dano, Suliani; Ida Sofiyanti (Universitas Ngudi Waluyo, 2024)
Continuity of Care in midwifery is a series of continuous and comprehensive service activities starting from pregnancy, childbirth, postpartum, New Born Baby (BBL) services and Family Planning (KB) services that connect women's health needs and the personal circumstances of each individual (Ningsih, 2017). The objectives of Continuity of Care are to monitor the progress of the pregnancy, ensure the health of the mother and the growth and development of the baby, recognize early any abnormalities or complications that may occur during pregnancy, reduce the use of interventions during childbirth including CS, increase the number of normal births compared to women who plan to give birth with action (Ningsih,2017) Midwives have an important task in improving maternal and neonatal health services in order to reduce maternal and infant mortality rates and improve the health status of mothers and babies. One way to improve health services is with comprehensive care for pregnancy, childbirth, postpartum and newborn babies and family planning services. In this study, the author used descriptive research methods, data collection techniques, namely through interviews, observations, physical examinations, supporting examinations, documentation studies and bibliography studies. The research started on 08 September 2023 during a visit from 1 mother and ended on 20 May 2024 during the implant method family planning service at the UPTD of the Ainiba Community Health Center. Comprehensive midwifery care is provided starting from pregnancy, childbirth, newborns, the postpartum period and family planning services. At TM III it was found that the mother was suffering from TB so the mother received category 1 OAT treatment. To prevent transmission during the baby's birth process, the mother was referred for a Caesarean section. Newborn babies, apart from breast milk, are also given formula milk so that mothers are encouraged to relax and improve position and attachment. The baby did not receive isoniazid prophylaxis so there was a gap. At the postpartum visit, dry technique surgical wound care and oxytocin massage and hypnobreast feeding were carried out because the mother was worried that her breast milk would not be enough. Mothers are advised to wear masks when interacting with babies. In providing birth control midwifery care, the mother was given counseling and decided to use the implant method of family planning at the UPTD Puskesmas Ainiba.. Continuous midwifery care (continuity of care) then always applies midwifery management, maintains and improves competence in providing care according to midwifery service standards Abstrak Continuity of Care dalam kebidanan adalah serangkaian kegiatan pelayanan yang berkelanjutan dan menyeluruh mulai dari kehamilan, persalinan, nifas, pelayanan Bayi Baru Lahir (BBL) serta pelayanan Keluarga Berencana (KB) yang menghubungkan kebutuhan kesehatan perempuan dan keadaan pribadi setiap individu (Ningsih, 2017). Tujuan Continuity of Care yaitu untuk memantau kemajuan kehamilan, memastikan kesehatan ibu dan tumbuh kembang bayi, mengenal secara dini adanya ketidaknormalan atau komplikasi yang mungkin terjadi selama hamil, mengurangi penggunaan intervensi pada saat persalinan termasuk SC, meningkatkan jumlah persalinan normal dibandingkan dengan perempuan yang merencanakan persalinan dengan tindakan (Ningsih, 2017). Upaya Bidan memiliki tugas penting untuk meningkatkan pelayanan kesehatan bagi maternal dan neonatal agar dapat mengurangi angka kematian ibu dan bayi serta meningkatkan derajat kesehatan ibu dan bayi. Salah satu cara untuk meningkatkan pelayanan kesehatan adalah dengan asuhan komperehensif dari kehamilan, persalinan, nifas serta bayi baru lahir dan pelayanan KB. Dalam asuhan ini penulis menggunakan metode penelitian deskriptif teknik pengumpulan data yaitu melalui wawancara, observasi, pemeriksaan fisik, pemeriksaan penunjang, studi dokumentasi dan studi daftar Pustaka. Penelitian di mulai pada tanggal 08 September 2023 pada saat kunjungan 1 ibu dan berakhir pada tanggal 20 Mei 2024 saat pelayanan KB metode implant di UPTD Puskesmas Ainiba. Asuhan kebidana yang dilakukan secara menyeluruh mulai dari kehamilan, persalinan, bayi baru lahir, masa nifas dan pelayanan KB. Pada TM III ditemukan ibu menderita TBC sehingga ibu mendapatkan pengobatan OAT kategori 1. Untuk mencegah penularan pada saat proses bayi lahir, ibu dirujuk untuk persalinan tindakan Sectio Caesar. Bayi baru lahir selain ASI juga diberikan susu formula sehingga ibu dianjurkan untuk relaktasi dan memperbaiki posisi dan perlekatan. Bayi tidak mendapatkan profilaksis isoniazid sehingga terjadi kesenjangan. Pada kunjungan nifas dilakukan perawatan luka operasi tehnik kering dan asuhan pijat oksitosin dan hipnobreastfeeding karena ibu merasa cemas ASI ibu tidak cukup selain itu. Ibu dianjurkan untuk memakai masker Ketika berinteraksi dengan bayi. Dalam memberikan asuhan kebidanan KB ibu telah diberikan konseling dan memutuskan untuk menggunakan KB metode implant di UPTD Puskesmas Ainiba. Asuhan kebidanan berkelanjutan (continuity of care) selanjutnya selalu menerapkan manajemen kebidanan, mempertahankan dan meningkatkan kompetensi dalam memberikan asuhan sesuai standar pelayanan kebidanan.